Effect of butylated hydroxy toluene on the quality of frozen goat semen - DEWRY, R K; DEKA, B C; BHUYAN, D; SINHA, S; BISWAS, R K; HAZARIKA, S B; BORAH, P; NATH, N C; DAS, A (The Indian Journal of Animal Sciences, 2015)
Ejaculates (40) collected from 5 Beetal bucks twice weekly were used to study the effect of 0 (control), 150, 200 and 300 μM butylated hydroxy toluene (BHT) on the quality of frozen semen by split sample technique. After removal of the seminal plasma, the semen was primarily extended with Tris extender (1: 5) considering the volume of semen prior to removal of seminal plasma and then split into four parts and finally extended with equal volume of Tris extender containing 0 (control), 300, 400 and 600 μM BHT. Consequent upon addition of equal volumes of Tris extender the rate of extension of semen rose to 1: 10 and eventual concentration of BHT in the extender was 0, 150, 200 and 300 μM. The extended semen was cooled gradually to 5°C @ 1°C/3 min and equilibrated in the cold handling cabinet for 4 h at 5°C. The extended semen was filled in French mini straws (0.25 ml) and polyvinyl alcohol powder of different colours were used for sealing the extended semen for identification of semen of different bucks processed with different concentrations of BHT. The freezing of semen was done by rapid horizontal vapour freezing technique using liquid nitrogen. The mean percent post thaw sperm motility, live sperm, live intact acrosome and HOST-reacted sperm were significantly higher in the extender with 200 μM BHT than with 150, 300 μM BHT and control. The release of ALT and AST from post thaw spermatozoa was also the lowest (33.75 ± 0.17 and 221.61 ± 0.73 U/L respectively) in the extender containing 200 μM BHT. Based on sperm motility, live sperm, live intact acrosome, HOST-reacted sperm, and ALT and AST release, 200 μM BHT in Tris extender was superior to 0, 150, and 300 μM BHT in freezing Beetal buck semen. It was concluded that BHT at 200 μM provided a better protection to the functional capacity of buck spermatozoa for cryopreservation.